Steady-state modeling of a microfluidic hydrogen reactor with immobilized TiO2-Pt photocatalyst mediated by iodine ions under ultraviolet (UV) irradiation - Yap, Kristian July R. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Photocatalytic water splitting to produce hydrogen is a promising renewable energy technology. Current experiments are usually conduced in large, closed-volume reactors connected to a gas chromatograph (GC) to monitor the gas products. Recently, researchers are exploring the use of a microfluidic platform to execute photocatalytic water splitting with the aim of increasing the photocatalytic efficiency. This work intends to lay the groundwork for using Computational Fluid Dynamics (CFD) modeling to aid the design and characterization of a microfluidic reactor for photocatalytic water splitting processes, particularly for hydrogen production. CFD modeling is known to be an effective tool for the design, optimization and scale up of photocatalytic reactors. To address the electron-hole recombination which can reduce photocatalytic activity, the partial Z-scheme system mediated by iodide (I) ions in basic medium was adopted using an immobilized TiO2-Pt photocatalyst under ultraviolet (UV) irradiation. Structural modeling using rectangular geometry was carried out through the built-in program in the computational software. The Finite Volume Method (FVM) was used to solve the conservation and species transport equations. The surface reaction rate was assumed to be pseudo-first order. Mass transfer efficiency in the microfluidic reactor was tested by varying the inlet flow rate and the aspect ratio at constant hydrodynamic residence time. The simulation results good agreement to literature data on hydrodynamics and photocatalyic hydrogen production in the microfluidic scale.
Thesis (M.S. in Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Photocatalysis; Water -- Purification -- Photocatalysis; Water -- Purification -- Ultraviolet treatment